Ways of resolving systemic crisis in economic theory - A. A. Yakovlev; A. V. Yakovlev (Russian Journal of Economics and Law, 2019)
Objective: modern economic science has been in a state of systemic crisis for many years. The reason is its empiricism, which limits the possibilities of economic science to a superficial description of the economic process. Numerous attempts of the economic science to exit from stagnation by means of this discipline per se did not lead to positive result. Our goal is to overcome the situation of “discontinuity” in the development of economic knowledge, which had formed by the end of the 20th century. Methods: abstract-logical, historical, methods of analysis and synthesis.Results: the paper proposes a way out of this situation by means of scientific methodology, which provides the opportunity to improve the specific discipline by using the power of the entire continuum of knowledge and methods developed by science during the whole period of its existence. The authors substantiate the necessity, admissibility and legitimacy of transiting to a scientific paradigm based on classification by certain types of relations and using the energy-dynamic theory for representing the transfer and transformation of any forms of energy, regardless of their belonging to a particular field of knowledge. In fact, we are talking about transition from empirical science to the one based on the study of links between processes and phenomena, as mathematics is not sufficient to describe their system features. It is indicated that the qualitative development of economic science can be provided only by studying objects as a set of elements with certain functions, which corresponds to the concept of “systems science”.Scientific novelty: the necessity is proved to transit to the science based on new ontology with the possibility to reach a higher level of abstraction. The ways of forming a new trajectory of economic theory development are designated; the theoretical methodology tools are presented providing formation of such theory. The proposed systemic dimension of science allows full-fledged elaboration of elements of any origin, regardless of the limitations within a scientific discipline.Practical significance: the paper shows that modern science has everything necessary for the withdrawal of economic science from the state of stagnation, which can be used by experts in the field of economics and related disciplines.